PELATIHAN SAFETY RIDING SEBAGAI LANGKAH KEAMANAN PELAJAR BERKENDARA - Suyitno Suyitno; Dwi Jatmoko; Aci Primartadi; Istya Ayu Ardiyanti; Widiyatmoko Widiyatmoko; Basuki Basuki; Yuli Widiyono (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
Safety riding is a safe driving behavior that can help to avoid traffic accidents. The purpose of safety riding is to increase rider awareness of all possibilities that may occur while driving. The stages of implementing this activity include: 1) Program needs analysis, 2) Activity planning. There have been several preparations made including intensive coordination with related local residents, the location of the program activities, and the time of program implementation. Everything is done by making a schedule to facilitate the implementation of further activities., 3) Implementation of activities by exposing safety riding material about driving safely and comfortably. Based on the results that have been carried out from planning, implementation to evaluation, it can be stated that community service activities are going well. From the results of the user questionnaire 1) Mastery of resource materials with a percentage score of 87 percent, 2) Timeliness of activities with a percentage score of 85 percent, 3) Material utilization with a percentage score of 95 percent, and 4) Participant satisfaction with a percentage score of 97 percent. Likewise with the results of the questionnaire the response of the participants averaged more than 75 percent. This shows that the activity went very well and satisfied the participants